2020
DOI: 10.1016/j.physa.2019.123228
|View full text |Cite
|
Sign up to set email alerts
|

Energy localization and excess fluctuations from long-range interactions in equilibrium molecular dynamics

Abstract: Molecular dynamics (MD) simulations of standard systems of interacting particles ("atoms") give excellent agreement with the equipartition theorem for the average energy, but we find that these simulations exhibit finite-size effects in the dynamics that cause local fluctuations in energy to deviate significantly from the analogous energy fluctuation relation (EFR). We have made a detailed analysis of Lennard-Jones atoms to track the origin of such unphysical fluctuations, which must be corrected for an approp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 103 publications
(184 reference statements)
2
12
0
Order By: Relevance
“…Numerically, by nanoparticles radius enhancing from 1 nm to 3 nm the aggregation time of these atomic structures decreases from 1.41 ns to 1.29 ns. The classic Navier-Stokes approach are usually used for the simulation of nanofluid flow and heat transfer; however the particle base methods like MD would show better performance at micro and nano scales levels [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Based on present work achievements, we can say the nanoparticle radius variation is an important parameter for using of Ar/Fe3O4 atomic structure in various industrial applications.…”
Section: Time Evolution Of Simulated Structuresmentioning
confidence: 80%
“…Numerically, by nanoparticles radius enhancing from 1 nm to 3 nm the aggregation time of these atomic structures decreases from 1.41 ns to 1.29 ns. The classic Navier-Stokes approach are usually used for the simulation of nanofluid flow and heat transfer; however the particle base methods like MD would show better performance at micro and nano scales levels [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Based on present work achievements, we can say the nanoparticle radius variation is an important parameter for using of Ar/Fe3O4 atomic structure in various industrial applications.…”
Section: Time Evolution Of Simulated Structuresmentioning
confidence: 80%
“…Thus, the basic requirements of standard statistical mechanics for fast coupling to a homogenous heat reservoir are absent for the primary response in most materials, including liquids, glasses, polymers, and crystals. Moreover, molecular dynamics (MD) simulations of crystals with realistic interactions exhibit excess energy fluctuations that diverge like 1/T as T → 0, deviating from standard statistical mechanics based on − / , but quantitively consistent with energy localization on length scales of nanometers [50]. Nanothermodynamics is necessary to treat independent subsystems that have a distribution of sizes, with realistic particles and heterogeneous interactions, allowing the laws of thermodynamics that govern statistical mechanics to be extended across multiple size scales, down to individual atoms.…”
Section: Standard Statistical Mechanicsmentioning
confidence: 84%
“…Other experiments show that glass-forming liquids have a separation of time scales between linear and rotational motion [37,38], suggesting that the two laws conserving momentum may also be uncoupled. Even in idealized single crystals, molecular dynamics simulations show that energy is persistently localized by anharmonic interactions [39], implying that energy localization will be even stronger in disordered systems. In any case, orthogonal dynamics in a simulation does not prohibit correlations between energy change and dipole rotation, it simply separates them so that they may proceed independently on their own preferred time scales.…”
Section: Orthogonal Dynamics With Intermittent Interactionsmentioning
confidence: 99%
“…Likewise, the London dispersion force that yields realistic van der Waals-like interactions requires quantum effects that involve overlapping wave functions between interacting molecules, and again this coherence is broken by wavefunctions that are localized. Classically, molecular dynamics simulations have shown that, even in idealized single crystals, anharmonic interactions yield significant deviations from standard fluctuation relations due to energy localization [39], which will be much stronger in non-crystalline systems.…”
Section: Orthogonal Dynamics With Intermittent Interactionsmentioning
confidence: 99%